Description of larva and pupa of Phylloicus cressae Prather 2003 (Trichoptera: Calamoceratidae) from a montane forest stream in the peri-urban area of Caracas, Venezuela - Barrios, Margenny C.; Mendoza, María D.; Montoya, José V. (Zootaxa, 2020)
Phylloicus is the most species-rich genus of the Neotropical Calamoceratidae. In Venezuela, twelve species are known from the adult stage and, from those, only one has its larval and pupal stages described. Here, we describe and illustrate the larva, pupa, and case of Phylloicus cressae, from a first order stream of the heavily disturbed Tuy River watershed in the peri-urban area of Caracas, northcentral Venezuela.